Improving the Lithography Sensitivity of Atomically Precise Tin‐Oxo Nanoclusters via Heterometal Strategy - Chen, Weizhou; Wang, Liming; Wang, Zi‐Rui; Zhu, Tao; Ye, Yuting; Li, Qiao‐Hong; Yi, Xiaofeng; Zhang, Jian (Angewandte Chemie International Edition, 2025)
Tin‐oxo clusters are increasingly recognized as promising materials for nanolithography technology due to their unique properties, yet their structural impacts on lithography performance remain underexplored. This work explores the structural impacts of heterometal strategies on the performance of tin‐oxo clusters in nanolithography, focusing on various metal dopants and their coordination geometries. Specifically, SnOC‐1(In), SnOC‐1(Al), SnOC‐1(Fe), and SnOC‐2 were synthesized and characterized. These clusters demonstrate excellent solubility, dispersibility, and stability, facilitating the preparation of high‐quality films via spin‐coating for lithographic applications. Notably, this work innovatively employs Atomic Force Microscopy‐based Infrared Spectroscopy (AFM‐IR), neutron reflectivity (NR), and X‐ray reflectivity (XRR) measurements to confirm film homogeneity. Upon electron beam lithography (EBL), all four materials achieve 50 nm line patterns, with SnOC‐1(In) demonstrating the highest lithography sensitivity. This enhanced sensitivity is attributed to indium dopants, which possess superior EUV absorption capabilities and unsaturated coordination environments. Further studies on exposure mechanisms indicated that Sn−C bond cleavage generates butyl free radicals, promoting network formations that induce solubility‐switching behaviors for lithography. These findings underscore the efficacy of tailored structural design and modulation of cluster materials through heterometal strategies in enhancing lithography performance, offering valuable insights for future material design and applications. The precise modification of tin‐oxo clusters via the heterometal strategy, specifically varying the metal dopants and their coordination geometries, has resulted in SnOC‐1(In), SnOC‐1(Al), SnOC‐1(Fe), and SnOC‐2, thereby tuning their distinct lithography performance.